Nanosericite as an Innovative Microparticle in Dual-Chemical Paper Retention Systems. (26th September 2013) - Perng, Yuan-Shing; Wang, Eugene I-Chen; Chang, Chih-Kai; Chang, Chih-Ping
Abstract : Dual-chemical retention systems based on 2 cationic polyacrylamides, a colloidal silica, and a globular anionic polymer microparticles were investigated and an exfoliated nanoparticle indigenous mica mineral, sericite, was examined for its efficacy in substituting commercial microparticle preparations. The results indicated that nanosericite generated FPR between 76.9 and 80.9% for fines and chemicals. Its ash retention values, however, were higher and tended to increase with doses of polymer, nanosericite, or Sc to between 16 and 24%. As for paper physical properties, nanosericite was not amenable to substitute the c-PAMb/polymer with only handsheet stiffness superior to the combination. Nanosericite, however, showed good substitution capacity than the c-PAMa-colloidal silica combination. Regardless of the c-PAMa doses, all examined handsheet physical properties incorporating nanosericite were superior to colloidal silica. The optimal performance was observed with c-PAMa dose of 200 ppm. Optical properties of the handsheets indicated that with nanosericite substitution, brightness values were comparable to the polymer group, while its substitution capacity for colloidal silica decreased with increasing c-PAMb dose. Only at c-PAMa dose of 300 ppm, it appeared to have good substitution for colloidal silica. Substituting nanosericite for colloidal silica appeared to reduce the c-PAMa charge and increased the overall cost effectiveness.